Influence of Socioeconomic Determinants on Access and Utilization of Family Planning Services among Women of Reproductive Age in Oyo West Local Government Area, Oyo State, Nigeria" - Daramola, Kolawole Tunmise; Olatunji, Muideen Babatunde; Adako-Iyanda, Olajumoke; Pelumi, Omoleye Tosin; Oluwaseyi, Aibinuomo Ayomide; Grace, Adeyeye Kehinde (American Journal of Biomedicine and Pharmacy, 2024)
Background: Family planning services are critical for promoting reproductive health and managing population growth. However, accessibility and utilization of these services among women of childbearing age remain significant challenges in many regions, including Oyo West, Nigeria. Limited access to family planning can lead to unintended pregnancies, increased maternal and child morbidity, and adverse socio-economic outcomes. Understanding the factors that influence the use of these services is essential for developing effective interventions and policies to enhance reproductive health. Objective: This study aimed to assess the utilization and accessibility of family planning services among women of childbearing age in Oyo West, examining demographic characteristics, socio-economic factors, and barriers to service use. Method of Analysis: A cross-sectional survey was conducted involving 300 women. Data were collected through structured questionnaires and analyzed using descriptive statistics to identify patterns in service utilization and accessibility. Results: The findings revealed that the mean age of respondents was 27.8 years, with 90% reporting poor accessibility to family planning services. A significant majority (70.1%) preferred natural family planning methods, while 59.8% indicated a preference for barrier methods such as condoms. Additionally, 70% of respondents highlighted inadequate information and education as barriers, and 65% experienced challenges related to service availability at health centers. Conclusion: The study highlights significant gaps in the accessibility and utilization of family planning services in Oyo West, emphasizing the need for targeted interventions to improve resource availability, enhance awareness, and address socio-economic barriers. These findings underscore the importance of comprehensive strategies to promote effective family planning service delivery.